Hall Scale in the Earth S Magnetosphere and Magnetospheric Substorm - Stepanova, M (John Wiley and Sons Inc, 2025)
We investigate the contribution of the Hall term on the generalized Ohm s law in magnetospheric plasmas. In particular, we focus on its role in processes that lead to the formation of substorm perturbations deep inside the magnetosphere. Using data from the THEMIS mission, we calculate the average Hall length (Formula presented.) and its spatial distribution near the equatorial plane. Our findings reveal that (Formula presented.) significantly exceeds the ion inertial length, which suggests that the Hall term s contribution to generalized Ohm s law is significantly greater than the convective term. In this case, the magnetic field lines are able to slip through the plasma, something that conventional magnetohydrodynamic models cannot adequately describe. We explore how such slippage facilitates the development of substorm perturbations that do not require changes in magnetic field topology. These perturbations include dipolarization of magnetic field lines, particle acceleration, electrojet formation, and other phenomena typically associated with substorms. © 2025. The Author(s).